O culto aos mortos como lugar teológico a partir do tratado : o cuidado devido aos mortos em Santo Agostinho - Bock, Vanderlei Mengue (2018)
The purpose of this paper is to reflect on the cult of the dead as theological locus. Our bibliographic research has its foundation on Saint Augustine`s treatise De Cura pro Mortuis Gerenda (On Care to be Had for the Dead) written in 421, in response to a query raised by bishop Pauline of Nola regarding the advantage of burying a christian near the grave of a saint or martyr. This paper is divided into three parts. The first deals with the meaning of the cult of the dead in the christian faith, including the concepts of prayer, reverence and the Communion of Saints in the light of the Tradition and Magisterium of the Church. In the second part, we present the key aspects regarding the cult of the dead in St. Augustine, especially the mediation between the living and the dead, augustinian theology about death and the meaning of the body according to his eschatology. The third part reflects on the cult of the dead as theological locus. It addresses the theological meaning of death, the liturgy of death, the sacredness of the corpse, the funeral celebrations and the meaning of the 7th day Requiem Mass, demonstrating that such cult favors the dead through prayer, the Communion of Saints, the importance of purgatory and indulgences, culminating in the resurrection of the body.